PENGARUH KUALITAS PRODUK DAN PENETAPAN HARGA TERHADAP KEPUASAN KONSUMEN (Studi Pada Produk Hijab Store Zoya, Mall Pekanbaru) - Ridho Yatul Jasmi; Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine how much the influence of product quality and pricing to consumer satisfactiont. Sampels in this study were taken as many as 100 respondens and techniques used was pusposive sampling approach. The data in this study using survey method through questionnares filled by consumers. Data were obtained by using simple regression analysis dan multiple regression analysis. The result of this study show that product quality has a significant impact on consumer satisfaction Pricing has a significant impact on consumer satisfaction. and then simultaneously product quality and pricing have a significant impact on consumer satisfaction. Subsequent research is suggested to use other methods in researcing consumer satisfaction, for example through in-depth interviews of respondents. Keywords: Product Quality, Pricing And Consumer Satisfaction